(untitled) (Scientific journal of the Fergana State University, 2024)
In this article, the first information about the agrotechnics of preparing introduced medicinal plant species for unfavorable climatic conditions is presented to the territory of the Fergana region. According to him, the stages of acclimatization of some promising medicinal plant species are mentioned.